Village Stakeholders Participation Values Education: An Action Research - (:unkn) unknown (ILEM, 2018)
Values are influential in people's behavior. The value perception of the individual's behavior is right or wrong as the show provides adoption. This shows how important education is in human behavior. In our country, it seems that values education studies are carried out independently of each other on the basis of institutions. This study, which focuses on social participation in the education of values, is based on an action study with primary school students and community groups in their environment. The aim of the study is to ensure that the applied values education program has a positive effect on the level of moral maturity of the students. The mosque was included as a stakeholder in the studies. In this context, studies about values education in the school have been done. At the same time, the same values are described in Friday khutbah. Quantitative and qualitative research methods have been used together. Initially, action research is planned. The needs of the sample were determined, the values to be included in the training program, and the Friday khutbah content to be used weekly. These actions have been discussed in the validity committee once every 15 days. The quantitative part of the study was pre-test and post-test. According to the results of the study, the 8-week study of the action was completed, and the results of the analyzes revealed that the students had an increase in the moral maturity scale' scores. The results of the analysis show that there is a significant difference between the pre- and post-implementation scores of the students who participated in the research on the Moral Maturity Scale (z=-2.26, p<.05). This difference observed when the rankings of the difference scores are taken into consideration seems to be in favor of the positive rankings, that is, the post-test scores.
Keywords: Value; morality; character education; action research; mixed method; values education; moral maturity; MORAL EDUCATION